Assessment genetic diversity of einkorn genotypes (Triticum monococcum L.) by gliadin electrophoresis - Gergana Nikolova DESHEVA; Bozhidar KYOSEV; Manol DESHEV (Acta Agriculturae Slovenica, 2020)
The genetic diversity of gliadins in twenty two einkorn accessions preserved under long-term seed storage condition in the National gene bank of Bulgaria were evaluated, using acid polyacrylamide-gel electrophoresis (Acid-PAGE). In total, 64 polymorphic bands and 22 gliadin patterns were identified. Thirty four different mobility bands and 21 gliadin patterns were identified in the ω-gliadin zone, 12 bands and 16 patterns were noted in the γ-gliadins, 17 patterns and 12 mobility bands were found for β-gliadins and six bands with five different α -gliadin patterns were determined. The genetic diversity index (H) was the highest for ω-gliadins (0.950), followed by β-gliadins (0.924) and γ- (0.914), respectively and the lowest value was detected in α-gliadin patterns (0.120). Cluster analysis based on the UPGMA method and Nei and Li similarity coefficients classified all the genotypes into 3 main groups. No relationships between genetic diversity, geographic origin and the genotypes were observed. The results of cluster analysis justify the high level of genetic variation among investigated einkorn accessions.